Ethnography from an Evolutionary Point of View - Salazar, Carles (Journal of cognition and culture, 2026)
The aim of this paper is to explore the possible collaboration between the cognitive and evolutionary human sciences and ethnography. My purpose is to show that certain kinds of behaviour and attitudes that can be observed by means of the ethnographic method can also be properly explained from an evolutionary perspective. I will explore the plausibility of an evolutionary point of view on ethnographic material by means of a case study: the analysis of the religious beliefs and practices of an Irish family. The theoretical proposal of this paper is twofold: first, that in this case we do not have one but two modes of religiosity, doctrinal and experiential; second, that ethnography can reveal the existence of the forms of popular religiosity that originate in the experiential mode of religiosity while an evolutionary perspective can explain their persistence.